Optimizing Digital Marketing for a Healthy Snack Business Through Collaborative Instagram Posts - Jett Lee Wilson; Adam Faturahman; Syifa Muthiatunnisa; Nuke Puji Lestari Santoso (ADI Bisnis Digital Interdisiplin Jurnal, 2026)
Increasing awareness of children’s health has shifted parents’ preferences from conventional snacks to healthier alternatives. The primary issue is that parents’ purchasing decisions are strongly influenced by trust and community validation. Social media has transformed from a platform for sharing information into an instrument of social validation that helps parents select products for their children. As an adaptive platform, Instagram introduced the collaboration post feature, enabling two accounts to jointly publish content. The urgency of this research lies in the challenge faced by brands in determining whether independently posting content is sufficiently effective or utilizing collaboration features is necessary to penetrate platform algorithms and reach audiences. This study aims to analyze the significant differences in Engagement Rate (ER) between Regular Post and Collaboration Post involving credible third parties, such as pediatricians, nutritionists, and mom influencers. The novelty of this research lies in optimizing the differences in the strategic functions of engagement and reach within collaborative social media marketing strategies. The analysis results indicate that regular posts are more effective in fostering community engagement, whereas collaboration posts are more effective in expanding audience reach. This finding is supported by the Independent Sample t-test, indicating a significant difference in engagement rates between regular posts and collaboration posts (t = 2.897; p = 0.010 < 0.05). Therefore, this study contributes to understanding the strategic trade-off between audience reach expansion and audience engagement levels in digital marketing strategies